2019
DOI: 10.1080/13662716.2019.1616533
|View full text |Cite
|
Sign up to set email alerts
|

Why do innovators not apply for trademarks? The role of information asymmetries and collaborative innovation

Abstract: This paper analyses the underlying reasons why innovators do not apply for trademarks for all of their valuable inventions. Using a unique database of UK innovations linked to innovative firms, the empirical analysis highlights the many ways that firms can alleviate information asymmetries and the constraints imposed by collaborative innovation without taking recourse to trademarks. When information asymmetries are not at stake, i.e. when firms use an already existing trademark for their innovations or when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
1
12
0
1
Order By: Relevance
“…Most empirical studies into the relatedness of trademarks and innovation pursued a cross-sectional approach and measured the firm-level use of trademarks with dichotomies: 'yes' or 'no'. There is an evident need for case studies that try to match innovation portfolios and trademark portfolios at the firm-level, to understand trademark propensities for various types and modes of open and closed innovation (see also Zobel, Lokshin, and Hagedoorn 2017;Athreye and Fassio 2019;Morales et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most empirical studies into the relatedness of trademarks and innovation pursued a cross-sectional approach and measured the firm-level use of trademarks with dichotomies: 'yes' or 'no'. There is an evident need for case studies that try to match innovation portfolios and trademark portfolios at the firm-level, to understand trademark propensities for various types and modes of open and closed innovation (see also Zobel, Lokshin, and Hagedoorn 2017;Athreye and Fassio 2019;Morales et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This is a wellknown issue that affect SMEs and startups most strongly (Block et al 2015a) and also can be found with the filing of other IP rights (de Rassenfosse and van Pottelsberghe de la Potterie 2013). Athreye and Fassio (2019) in this special issue investigated a broad set of innovative firms and suggested how two factors explain the decision not to trademark. On the one hand, innovators might already have protected their positions in other ways and will not file for a separate trademark for a new innovation project.…”
Section: Appropriation Of Rents As a Motive (Innovation Perspective)mentioning
confidence: 99%
“…Explicitly, an enterprise with an EO is involved in the creation of groundbreaking products, methods, and tactics, many of which could be patented, trademarked, etc. [72]. Similarly, an enterprise with an EO is agreed to be identifying, creating, measuring, and taking advantage of prospects [73].…”
Section: Entrepreneurial Orientation and Intellectual Propertymentioning
confidence: 99%
“…Lunney (2018) who identifies two tiers in trademark systems, in which both parties can afford to litigate in the upper tier, but only one party can in the lower tier. It has been argued by Athreye and Fassio (2020) that while trademarks share the same characteristics of exclusivity as patents, trademarks protect a quite different kind of market failure (viz. the information asymmetry between buyer and seller), allowing the protection of both incremental and service innovations.…”
Section: Introductionmentioning
confidence: 99%